Pengaruh Audit Tenure, Auditor Switching dan Ukuran KAP terhadap Audit Report Lag pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Insani, Satya; Arza, Fefri Indra; Sulaiman, Ahmad Rahbani (Universitas Negeri Padang, 2025)
This study aims to determine the effect of audit tenure, auditor switching and KAP size on Audit Report Lag. Audit Report Lag is the dependent variable, while Audit Tenure, Auditor Switching and KAP Size are independent variables. Audit Report Lag is measured by the Date of issuance of the audit report-the company's closing date. Audit tenure is measured by calculating the number of years of engagement between the client company and the auditor at the KAP. Auditor Switching is measured by a dummy variable, 1 for companies that do auditor switching and 0 for companies that do not do auditor switching. KAP size is measured using a dummy variable, 1 for companies that use Big Four KAP and 0 for companies that use non-Big Four KAP. The data used are annual reports and financial statements of Property and Real Estate companies listed on the Indonesia Stock Exchange in 2020-2023, with a sample of 88 companies. Data analysis using purposive sampling and multiple linear regression. The results of the study indicate that Audit tenure has a significant negative effect on audit report lag, Auditor switching has a significant negative effect on audit report lag, KAP size has a significant negative effect on audit report lag.